Caffeic Acid Phenyl Ester (CAPE) Protects against Iron-Mediated Cellular DNA Damage through Its Strong Iron-Binding Ability and High Lipophilicity - Bo Shao; Li Mao; Miao Tang; Zhu-Ying Yan; Jie Shao; Chun-Hua Huang; Zhi-Guo Sheng; Ben-Zhan Zhu (MDPI AG, 2021)
Caffeic acid phenethyl ester (CAPE) and its structurally-related caffeic acid (CA), ferulic acid (FA) and ethyl ferulate (EF) are constituents of honeybee propolis that have important pharmacological activities. This study found that CAPE-but not CA, FA, and EF-could effectively prevent cellular DNA damage induced by overloaded iron through decreasing the labile iron pool (LIP) levels in HeLa cells. Interestingly, CAPE was found to be more effective than CA in protecting against plasmid DNA damage induced by Fe(II)-H2O2 or Fe(III)-citrate-ascorbate-H2O2 via the inhibition of hydroxyl radical (•OH) production. We further provided more direct and unequivocal experimental evidences for the formation of inactive CAPE/CA-iron complexes. CAPE was found to have a stronger iron-binding ability and a much higher lipophilicity than CA. Taken together, we propose that the esterification of the carboxylic moiety with phenethyl significantly enhanced the iron-binding ability and lipophilicity of CAPE, which is also responsible for its potent protection against iron-mediated cellular DNA damage. A study on the iron coordination mechanism of such natural polyphenol antioxidants will help to design more effective antioxidants for the treatment and prevention of diseases caused by metal-induced oxidative stress, as well as help to understand the structure-activity relationships of these compounds.